2001
DOI: 10.1034/j.1399-6576.2001.450216.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient neurologic symptoms after spinal anaesthesia using isobaric 2% mepivacaine and isobaric 2% lidocaine

Abstract: In this study TNS was associated with isobaric mepivacaine 20 mg/ml, with an incidence of 7.5%, and with isobaric lidocaine 20 mg/ml, with an incidence of 2.5%, in patients having orthopaedic procedures in the supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 38 publications
(62 reference statements)
3
27
0
3
Order By: Relevance
“…31 Results from smaller randomized blinded trials have demonstrated rates of TNS ranging from 0 to 7.4%. 10,18,32,33 Reported risk factors for the development of TNS include outpatient status, obesity, lithotomy, and knee arthroscopy position. 34,35 In the present study, no patient reported symptoms consistent with TNS despite some of our enrolled patients having many of the reported risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…31 Results from smaller randomized blinded trials have demonstrated rates of TNS ranging from 0 to 7.4%. 10,18,32,33 Reported risk factors for the development of TNS include outpatient status, obesity, lithotomy, and knee arthroscopy position. 34,35 In the present study, no patient reported symptoms consistent with TNS despite some of our enrolled patients having many of the reported risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The study population was not large enough to discover any difference in the occurrence of rare side-effects such as TNS. After lidocaine spinal anesthesia, the reported incidence of TNS has varied from 0% to 40% [26,27]. Although the anesthetic characters are quite similar with articaine and lidocaine, TNS rate was lower in articaine than lidocaine and the Cesarean section in such a short operation may be preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatif ilk günlerde görülen bu komplikasyonların insidansı, muhtemel sebepleri, risk faktörleri ve tedavisi anestezistlerin ilgi odağı haline gelmiş ve çok sayıda çalış-manın konusu olmuştur. [9][10][11] Başlarda, lidokainle spinal anestezi uygulanan hastalarda derlenme sonrası izlenen bu durum ''geçici nörolojik toksisite'' olarak adlandırılmış, [7,8] irritasyon'' [6] ve son olarak ''geçici nörolojik semptom'' [12] olarak literatüre geçmiştir.…”
Section: Discussionunclassified